Living Curriculum Shifts in Arts Education: From Knowledge Transmission to Worldview Sharing - Yoon, Ji Hye (Journal of the Canadian Association for Curriculum Studies, 2020)
Drawing upon narrative inquiry into the lived experience of an artist becoming an arts teacher, this research investigates curriculum in arts education. Its focus is the teaching experiences of a professional photographer in the process of becoming a photography teacher. This research began with two teaching assumptions about curriculum. The first was an acquisition-orientation to teaching; knowledge transmission that changes students’ state from unknowing to knowing. The second was a making-orientation to teaching; methods and techniques training that allows students to replicate or produce knowledge. The first emphasized content while the second emphasized how students apply it. These assumptions eventually changed until they emerged as a communication-orientation to teaching that focuses on interaction with students and a sharing-orientation to teaching that engages dialogue between teacher and students instead of teacher monologue. With a communication-orientation and sharing-orientation to teaching, students became curriculum makers rather than curriculum receivers. These shifts in orientation meant students could share “their own stories” together with their own photographs, thus composing valuable narratives for the study—narratives that provided insight into how they see the world. Arts education is not only about transferring knowledge from teacher to students, but about sharing feelings with students. A communicating and sharing curriculum makes possible an encounter of minds between teacher and students, which was conceptualized as “relationship of minds” in this research. It enables us to better understand teaching and curriculum.